2019
DOI: 10.33102/jfatwa.vol16no2.7
|View full text |Cite
|
Sign up to set email alerts
|

Model Institusi Pendidikan Melalui Sinergi Dana Wakaf dan Zakat di Malaysia

Abstract: Education is a main asset in the growing and development of a country. Various financial resources from the government and private agencies are provided to ensure that all Malaysians have the opportunity to obtain education and further their studies. Waqaf and zakat are one of the most important contributors in education. There have been many efforts undertaken by waqaf and zakat institutions in the development of education sector such as helping the B40 and underprivileged gorup. Therefore, this study will di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 2 publications
0
2
0
Order By: Relevance
“…As a result, zakat has become the primary reason many students can continue their education and achieve academic excellence. This is supported by studies such as Ab Rahman and Anwar (2014), who found that zakat played a crucial role in promoting educational achievements among poor students.…”
Section: Literature Reviewmentioning
confidence: 72%
“…As a result, zakat has become the primary reason many students can continue their education and achieve academic excellence. This is supported by studies such as Ab Rahman and Anwar (2014), who found that zakat played a crucial role in promoting educational achievements among poor students.…”
Section: Literature Reviewmentioning
confidence: 72%
“…However, OPZ synergy gets inadequate attention so far and attention is paid to how to maximize the zakat management. Synergy is required between OPZ and muzakis on which the attention focused so far, including discussing the synergy between zakat and tax and synergy between zakat (Islam Compulsory) and infak, awqaf (Islam Voluntary) (Ab Rahman et al, 2019;Malik, 2020;Mustofa and Fata, 2015).…”
Section: Faizatul Ansoriyah Kushandajani Hartuti Purnaweni Retno Sunu...mentioning
confidence: 99%